Evaluation of uterine cervical cancer in pregnancy: A cross-sectional study. (March 2020) - Vasques, Rafaela B.; Carramenha, Luiza L.; Basílio, Ivo; Leão, Maria Eduarda B.; Carvalho, Gabriela P.S.L.; Amaral, Raquel M.C.; Rezende-Filho, Jorge; Guerra Neto, Nereu G.M.; Furtado, Yara L.
Abstract: Objective: Evaluate the prevalence and the regression rate of cytological alteration in pregnant patients below the recommended age by the Brazilian Guidelines for the Screening of Uterine Cervical Cancer Guideline in the prenatal service of Maternidade Escola da Universidade Federal do Rio de Janeiro. Study design: We included the cytopathological exams of all pregnant patients that attended on the outpatient from January 2010 to May 2016. For the identification of the pregnant women, the Management and Integrated System and the Uterine Cervical Cancer Information System of the institution were used. We performed X 2 test. The level of significance was 0.05. Results: The study totaled 5825 cytopathological exams, of which 1822 were from pregnant patients ≤ 24 years of age. Only 4.06 % (74/1822) of altered results were found (p < 0.05). The most frequent change was low-grade squamous intraepithelial lesion with a prevalence of 1.92 % (35/1822) whereas high-grade squamous intraepithelial lesion had 0.16 % (3/1822). The regression rate in pregnant patients ≤24 years of age was 34, 32 %. Conclusion: There was a low prevalence of cytological abnormalities in pregnant patients ≤ 24 years, low frequency of high-grade squamous intraepithelial lesion among the altered cytologies and a high spontaneous regression rate, therefore screening is not recommended before the age determined by the Brazilian Guideline.